Enhancing Public Services in the West Java Provincial Government: Unraveling Challenges, Defining Essence, and Proposing Solutions - Engkus, Engkus (UIN Sunan Gunung Djati Bandung, 2023)
Public service is the linchpin of good governance, profoundly impacting community quality of life. This research delves into the redefinition of public service within the West Java Provincial Government, scrutinizing its essence and confronting primary challenges to effective service delivery. Amidst hurdles like intricate bureaucracy, deficient inter-agency coordination, and incongruent service standards, understanding these issues is imperative for a nuanced comprehension of public service. The research objective is to meticulously explore and redefine the core of effective public service at the West Java Provincial Government level, establishing a foundation for comprehending factors influencing service quality. Employing a qualitative approach encompassing in-depth interviews, observations, and document analysis, the study aims to gain profound insights into perceptions, experiences, and practices related to public service at the provincial government level. The findings pinpoint key aspects contributing to a comprehensive definition of public service. Recommendations derived from these findings propose initiatives to augment inter-agency coordination, streamline bureaucratic processes, and enhance consistency in service standards, thereby bolstering the efficacy of public service in the West Java Provincial Government. This research aspires to significantly contribute to fortifying the understanding and implementation of more effective, sustainable, and responsive public services to cater to the community's needs within the West Java Provincial Government area.